(untitled) (American Journal of Islam and Society, 2005)
Why should I, your after-dinner speaker, a time for dessert – for sweetness – be the bearer of exclusively bad news, of chapters from the contemporary chaos that seemingly surrounds us. “The Darkness that Surrounds Us,” to call upon the words of a great American poet Robert Creeley, who, I imagine, never would have imagined that his own troubling personal vision would become an easily recognized metaphor to be invoked, as I invoke it, at a gathering of Muslim social scientists. Well, there are some good signs, like a nice after dinner mint that one discovers tucked just under one’s plate at the end of the meal, and I will get to them. My assumption is that I am really not here to tell you of things you know, living as you do in the United States … things you know far better than I, particularly since, as a journalist, I feel on safest ground when I report to you from personal experience. I cannot and will not even begin to address the many moments of humiliation and pain that many American Muslims have experienced in the backlash to 9/11 and the events that have followed, precisely because I have been personally spared any those experiences. So, I will address experiences from which I have not been spared. I have lived abroad, in what could be called the Arab-Islamic world, for forty years. And for me, the trajectory of contemporary chaos and the crisis confronting the Muslim youth has been a long one, long before 9/11. More than half of those years in the Middle East were spent as a journalist, mainly ...